Evaluation of Success Factors for Academic Information System Applications in Higher Education Using the Hot-Fit Model - Sry Dhina Pohan; Ircham Ali; Siska Ayu Widiana; Supriyanto; Yusuf Wahyu Mandaya (Universitas Negeri Semarang, 2025)
This research explored the adoption of the HOT-Fit paradigm and its influence on the success of an academic information system application in higher education. Using the PLS-SEM multivariate data analysis approach, the HOT-Fit model was evaluated in order to investigate the foundations of theory from a prediction standpoint. This was done to find out more about the model's potential applications. The HOT-Fit method takes various elements into account when performing a system analysis. Humans, organizations and technology are integrated elements and must be considered for the continued existence of an operating entity. This study uses hypothesis testing on a total of ten hypotheses to show the relationship between Academic Information System variables. The results show that six of the investigated hypotheses have a significant effect, while the other four are discarded because they are not relevant. 7.344 is the variable value of customer satisfaction. Program Features and Benefits The use of a variable with a value of 0.426 contributes little to the overall clarity of the situation. Based on the results of demo data processing, 121 participants (76.58%) reported good results, 13 (8.13%) rated this system as good, and 24 (15.19%) rated it as bad, resulting in a disparity between user expectations and the situation.